Exploring The Effectiveness of Telemedicine as A Hospital Strategy in Bali - I Wayan Artha Pradana; Ida Ayu Oka Martini (Jurnal Manajemen dan Bisnis, 2022)
The Covid-19 pandemic has prompted an adaptation of new habits. In the health sector, telemedicine has developed into an option to reach health services. Health practitioners and patients are getting used to using telemedicine. However, with the easing of the pandemic situation in the new normal era, the sustainability of telemedicine is a concern. This study aims to determine the effectiveness of telemedicine for its users and how telemedicine can be a strategy for hospitals. This research uses a qualitative descriptive method. Respondents in this study consisted of hospital leaders, specialist doctors, and patients at several hospitals in Bali. Validation of data using triangulation technique. SWOT analysis is used to analyze telemedicine as a hospital strategy. The results of this study found that telemedicine was felt to be effective for use as a health service. This is based on the user's perceived benefits and success in meeting health care needs. As a hospital strategy based on SWOT analysis, telemedicine has strong strengths and opportunities compared to its weaknesses and threats. Telemedicine has become an effective health service for patients and health practitioners. As a strategy, hospitals can develop telemedicine to be even more advanced by improving quality that prioritizes cost efficiency, time, and effectiveness of therapy. This is based on the user's perceived benefits and success in meeting health care needs. As a hospital strategy based on SWOT analysis, telemedicine has strong strengths and opportunities compared to its weaknesses and threats. Telemedicine has become an effective health service for patients and health practitioners. As a strategy, hospitals can develop telemedicine to be even more advanced by improving quality that prioritizes cost efficiency, time, and effectiveness of therapy. This is based on the user's perceived benefits and success in meeting health care needs. As a hospital strategy based on SWOT analysis, telemedicine has strong strengths and opportunities compared to its weaknesses and threats. Telemedicine has become an effective health service for patients and health practitioners. As a strategy, hospitals can develop telemedicine to be even more advanced by improving quality that prioritizes cost efficiency, time, and effectiveness of therapy.